The Influence of Affiliate Marketing and Brand Image on Impulse Buying Skintific Products on Shopee Live in Generation Z - Dewi Inda Sari (INCOME: Innovation of Economics and Management, 2023)
The internet is now a modern lifestyle phenomenon in everyday life, the ease in accessing the Internet then raises the idea that in searching for information the Internet is as the primary source of reference. Seeing a fairly good opportunity in the e-commerce industry, various companies that operate in the field of e-trade are also emerging. It is known that there was a significant increase in e-commerce transactions in Indonesia where the study also obtained information that Indonesians prefer to shop online. Besides, women are happier when buying products in e-commerce including skincare products that are skintific. The research method used in this research is the quantitative method, which can be defined as a kind of research that is systematic and structured with clear stages, aimed at describing a social phenomenon that exists. Reviewed from the purpose of this research is categorized as research testing hypothesis while the approach used is descriptive quantitative. In this study, researchers used questionnaire techniques that were distributed or given to live audiences or users on skintific products. The Sampling technique used is probability sampling. The number of samples taken is 100 respondents. Research results show that there is a significant influence between affiliate marketing and brand image on impulse buying Skintific products on Shopee Live on Generation Z